Negotiating wage inequality in Slovakia - Martiskova, Monika; Kahancová, Marta; Sedláková, Mária (Bratislava, 2017)
"This report was financed by European Commission Grant no. VS/2014/0538. The report appeared earlier as NEWIN Country Report: Slovakia (2016)."